A Successfully Treated Case of Gorham-Stout Syndrome with Sternal Involvement - Kim, Bong Jun (Korean J Thorac Cardiovasc Surg, 2015)
Gorham-Stout Syndrome (GSS) is a rare disease characterized by localized bone resorption. Any part of the skeleton may be affected; therefore, symptoms can vary depending on the site involved. Pathological analysis reveals lymphovascular proliferation and osteolysis in the affected lesion, but the etiology of the disease is poorly understood. When GSS occurs in the chest, chylothorax or respiratory failure may occur. Thus far, a standard treatment for GSS has not been established, and the prognosis remains unknown. The following case report describes a successfully treated case of GSS in a 16-year-old boy with an affected sternum and ribs.